1980
DOI: 10.1039/dt9800001243
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the electrochemical and pulse-radiolytic oxidation of the complexes of nickel(II) and copper(II) containing 1,4,8,11-tetra-azacyclotetradecane

Abstract: Electrochemical and pulse-radiolytic oxidation of [ N i ( c y ~I a m ) ] ~+ and [Cu(cyclam)12+ (cyclam = 1,4,8,11tetra-azacyclotetradecane) have been studied in aqueous acidic perchlorate and sulphate media. As with other nickel macrocyclic systems, [ N i ( c y ~I a m ) ] ~+ is oxidized to Ni*'I, the stability of which is enhanced by sulphate complexation. In contrast, [Cu(~yclam)]~+ is much less stable than the nickel analogue and does not form a stable sulphate complex. Electrochemical oxidation of [Cu(cycla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…The value obtained for the corresponding nickel complex of cyclam, [Ni(6)] 2ϩ , is 459 nm. This cation 12,13 has been well documented to be square planar in both the solid state 14,15 and (in the absence of coordinating anions) also in aqueous solution; 16 in the latter solvent the absorption maximum in the visible region occurs at 450 nm (ε = 45 M Ϫ1 cm Ϫ1 ).…”
Section: Uv-vis Spectral Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The value obtained for the corresponding nickel complex of cyclam, [Ni(6)] 2ϩ , is 459 nm. This cation 12,13 has been well documented to be square planar in both the solid state 14,15 and (in the absence of coordinating anions) also in aqueous solution; 16 in the latter solvent the absorption maximum in the visible region occurs at 450 nm (ε = 45 M Ϫ1 cm Ϫ1 ).…”
Section: Uv-vis Spectral Propertiesmentioning
confidence: 97%
“…The residue was recrystallized from a mixture of dichloromethane and methanol to yield red-purple crystals (0.30 g, 60%). Single crystals suitable for X-ray diffraction were obtained from dichloromethane-methanol (1 : 1) (Found: C, 42.68; H, 6.70; N, 16.89. C 17.5 H 32 CuN 6 O 6.5 requires C, 42.55; H, 6.53; N, 17.01%).…”
Section: Metal Complex Synthesismentioning
confidence: 99%
“…6 relatively fast in a second-order process. [12][13][14] In order to inhibit the last reaction it seemed that the preferred route of preparing the column is by the sol-gel entrapment procedure.…”
Section: A C H T U N G T R E N N U N G (H 2 O) 2 ]mentioning
confidence: 99%
“…As sulfate was shown to stabilize [Ni III (L i )] 3+ ( i = 1, 2, 7),22,23,27,28 it seemed of interest to investigate the difference in behaviour of the two [Ni III (cyclam)] 3+ isomers. CV and square‐wave experiments showed that the trans ‐ III ‐[Ni III (cyclam)] 3+ isomer as expected for the relative symmetrical octahedral environment, binds two sulfate anions (Figure 5) with K = 2 × 10 6 M –2 , the CVs are reversible.…”
Section: Resultsmentioning
confidence: 99%